Telerehabilitation as a Method for Achieving Competencies in Physical and Rehabilitation Medicine Residency Training in a Developing Country: A Protocol for a Pilot Mixed-Methods Study - Leochico, Carl Froilan D.; Carlos, Frances Ann B.; Tiangco, Anna Cecilia S. A.; Supnet, Isabella E.; Ignacio, Sharon D.; Mojica, Jose Alvin P.; Rey-Matias, Reynaldo R. (Frontiers in Rehabilitation Sciences, 2022)
Background In the second year of the COVID-19 pandemic, Physical and Rehabilitation Medicine (PRM) residents in a developing country continue to face a lack of in-person clinical exposure and learning opportunities. With the unprecedented shift to virtual care, it remains uncertain whether residents can achieve PRM competencies using telerehabilitation as a method of instruction. Objective To determine the PRM residents' ability to achieve competencies through telerehabilitation, as perceived by different stakeholders (residents, chief residents, training officers, and department heads). Methods This will be a pilot mixed-methods study, employing concurrent triangulation, in the Department of Rehabilitation Medicine in one large private medical center and one large government hospital in Manila, Philippines. There will be two phases of online data collection upon approval by their respective research ethics board. The first phase will involve an online Likert-scale questionnaire to obtain the residents' self-perceived attainment of competencies and learning of PRM topics and skills specified by the International Society of Physical and Rehabilitation Medicine and the Philippine Board of Rehabilitation Medicine. The results of the survey will then be summarized and presented in a focus group discussion (FGD) with the department heads, training officers, and chief residents of the two institutions in an attempt to explain the residents' perceptions on their competencies achieved through virtual care. Afterwards, the qualitative data obtained from the FGD will then be thematically analyzed, and mixed methods integration will be employed to generate knowledge and recommendations. Discussion It is hypothesized that the majority of the residents had little to no experience with telerehabilitation pre-pandemic. Suddenly telerehabilitation was used to augment clinical training during the pandemic. It is uncertain whether telerehabilitation can help residents achieve competencies in the different domains of training, namely: patient safety and quality patient care; medical knowledge and procedural skills; interpersonal and communication skills; practice- and systems-based learning and improvement; reintegration of people with disabilities into the society; medical ethics and public health; quality assurance; policies of care and prevention for disabled people; and professionalism. The study results can provide insights on the aspects of a PRM curriculum that may have to be modified to ensure the training program is sensitive and appropriate to the changing training needs of the residents amid the pandemic and similar crises that may disrupt in-person clinical encounters in the future.